Excellent high-temperature strength of (HfZrTiTaNb)C high-entropy carbide diffusion-bonded joint via in-situ alloying of Ni/Nb/Ni composite interlayer - Ruijie Mu; Ying Wang; Shiyu Niu; Kongbo Sun; Zhenwen Yang (Journal of Advanced Ceramics)
To obtain high-entropy carbide (HEC) joints with excellent high-temperature performance, a (HfZrTiTaNb)C HEC joint featuring a direct diffusion-bonded interface with a Nb-based interlayer was successfully fabricated at relatively low temperatures of 1150–1250 °C for 60 min under 10 MPa. Starting from a modified Ni/Nb/Ni composite interlayer with a Nb content of > 64 at%, an alloyed Nb2Ni layer was constructed in situ by accelerating the directional diffusion of Ni atoms from the high-entropy interface into the remaining pure Nb through the Ni‒Nb eutectic liquid. Moreover, the excess liquid phase was squeezed out of the bonding region, ensuring the absence of Ni-based compounds. Leveraging the intrinsic interfacial stability and sluggish diffusion effect, the HEC with its original lattice structure, was capable of developing diffusion bonding with the Nb2Ni layer instead of interacting with the liquid phase. The high reliability of the HEC/Nb2Ni bonded interface was confirmed by the coherence of (11¯3) HEC//(141)Nb2Ni and a calculated lattice misfit of 0.044. The HEC joint had a high room-temperature strength of 174 MPa because of the homogenous Nb2Ni layer, which exhibited nanohardness (15.2±1.5 GPa) and an elastic modulus of 219.9±17.5 GPa. Furthermore, the strength of the HEC joint did not decrease at 1000 °C, increasing by ~49% over that of HEC/Ni/HEC diffusion-bonded joints, which have stringent surface flatness requirements. This suggested that the HEC/Nb2Ni interface had excellent resistance to high-temperature softening, even though it was invariably the initial failure location. This work is informative for designing bonding structures and preparing HEC components.